URBAN REGENERATION FINANCING IN MALAYSIA - Sabariah Eni; Muhammad Najib Razali (PERINTIS eJournal, 2021)
Property development is seen as one of the key element in urban regeneration process in halting decline in town and cities. Moreover, the regeneration policy is viewed as a key driver of economic, physical and social growth. Thus, it is an expansive and pervasive measure to policy making decisions. Post 2007 sets the challenges as Global Financial Crisis (GFC) led to the uncertainty and financial constraint for urban regeneration. The traditional practice to finance the development is by way of public investment. This places a huge burden on governments in terms of raising sufficient investment. In the face of continuing economic crisis, this study examines alternative funding vehicles to fund urban regeneration projects. One possible alternative financing tool is Land value capture (LVC). This study explores an alternative financing mechanism designed to capture the uplift in land value due to development activity. This study also examines the application of value capture in terms of its prospect and challenges in Malaysia. Furthermore, this paper provides the first comprehensive empirical investigation in urban regeneration financing and LVC in Malaysia. The analysis also identifies various LVC mechanisms that are applied around the world and their potential for application in Malaysia.